Muslims as terrorists : hate speech against Muslims - Tamsila Naeem (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study aims to analyze the diplomatic use of hate speech acts against Muslims by Western communities, who is to establish their power over Muslims, declare Muslims as terrorists, extremists and fundamentalists in their media, literature and political debates. They have prejudice against Muslims, which is reflected in their socio-political behavior. Muslims all over the world get psychologically disturbed, since such derogatory speeches, abusive titles and bigotry practices against them deconstruct their archetypal identity as peace loving community to terrorists. The hypothetical framework functional in this study is based on the Judith Butler’s Theory of Excitable Speech, promoted by her in 1997. The study is both quantitative and qualitative centered on a mixed survey method, which comprises 25 close-ended questions along with the views of the selected respondents. The outcomes of the research demonstrate that antiIslamic forces try to suppress Muslims in order to psychologically subjugate them. The study recommends that appropriate consideration should be given to uphold Muslim identity. Additionally, all the communities need to confiscate differences among them to cultivate a culture of peace in the world.